Oxford guide to British and American culture (Oxford, 1999)
The book presents over 10.000 encyclopedic entries on British and American history, literature and the arts, legends and customs, places, institutions, sport, entertainment, and every day life; over 250 longer articles on topics such as education, fashion, Hollywood, humor, industry, politics, religion, and Shakespears; 526 photographs and illustrations; 32 pages illustrated with colour photographs and maps.
Keywords: america,america,gt. britain,gt. britain; economic aspects,encyclopedias,social conditions,encyclopedias,economic aspects,encyclopedias,social conditions,encyclopedias